Vamos aos fatos: funcionamento discursivo a partir do método de checagem de informações - Rodrigues, Lucas Andrey (2024)
This work is the result of research on the journalistic discursive functioning of the factchecking media Aos Fatos, which centers its journalistic practice on fact-checking. The research corpus consists of eighteen Discursive Sequences (hereinafter, SDs) related to the discourses present in the sections "Our Method" (methodological description), "We Check," "Who We Are," and two news articles taken from Aos Fatos' Instagram page. The idealized objective and transparency that Aos Fatos maintains about its journalistic activity motivated us to develop this research. Therefore, the main objective was to analyze the discursive functioning of Aos Fatos to understand the discursive positions it occupies when disseminating discourses. Grounding our analytical gestures from the theoretical perspective of French Discourse Analysis, proposed by Michel Pêcheux, we were able to understand how Aos Fatos establishes effects of meaning that indicate its insertion into the memory network of mainstream journalistic practices. This is because its practice is constituted by discourses already circulating in the digital environment, under the illusion of transparent and objective language, maintaining itself in a journalistic imaginary of reliable media, governed by impartiality and regarded as a truth maintainer. The analyzed meanings point, therefore, to the impossibility of Aos Fatos belonging to a space outside the ideological realm, as the interpretive gestures applied in the construction of fact-checks constitute the discursive and ideological affiliations reflected in Aos Fatos' media discursive practice.